Harnessing pro-inflammatory and immunopathologic immune responses in urinary tract infections for vaccine development: it’s all about a balance - Periasamy, Sivakumar; Lübbers, Joyce; King, Susan; Hovingh, Elise S.; van der Fits, Leslie; van den Dobbelsteen, Germie P. J. M. (Frontiers in Immunology, 2026)
Urinary tract infections (UTIs) cause a high economic burden with frequent medical visits, and in severe cases can lead to hospitalization due to complications like bacteremia or sepsis. UTIs are treated with antibiotics; however, this contributes to the emergence of antimicrobial resistant (AMR) bacterial strains because of misuse and overuse of antibiotics. Uropathogenic E. coli (UPEC) is the most common cause of UTIs and is commonly associated with antibiotic resistance. Several host defense mechanisms including the urothelial barrier, antimicrobial peptides, and complement protect the urinary tract from infection. If UPEC is encountered, a pro-inflammatory immune response starts to combat the infection, with antimicrobial peptides and protein as a first line of defense followed by the activation of the innate and adaptive immune responses. These innate and adaptive immune responses are sometimes inadequate during established UTI, and recurrence of UTI is common. In addition, an overactivation of the immune response to UPEC causes immunopathologic damage to tissues and cells. Anti-E. coli vaccines have been proposed as an ideal approach both to improve the immune response to infection and to limit the emergence and spread of AMR strains. Currently, a few UTI vaccines have been licensed in a couple of countries but are not broadly approved and novel vaccines are being explored. In this review, we focus on the pro-inflammatory response to UPEC infections and the immunopathologic effects of an overactive pro-inflammatory response during UTIs in humans. We highlight the components of the immune response during UTI that can be utilized for the development of a preventative UPEC vaccine.